New Generalizations of the Choquet Integral by Restricted Dissimilarity Functions - Lucca, Giancarlo; Asmus, Tiago; Dimuro, Graçaliz P.; Santos, Helida; Reiser, Renata S. H.; Yamin, Adenauer C.; Marco-Detchard, Cedric; Bustince, Humberto (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2025: Anais da XXXV Brazilian Conference on Intelligent Systems, 2025)
This paper introduces new generalizations of the Choquet integral by Restricted Dissimilarity Functions (RDFs) to construct alternative fusion operators. The Choquer-RDF-Based generalization where applied in the Fuzzy Reasoning Method (FRM) of a Fuzzy Rule-Based Classification System (FRBCS) to cope with a benchmark composed by 33 different datasets. The results indicated that this approach is an alternative to generalizations that are based in the difference operator, considered in the original functions.